IJCM_21A: How do under-five children belonging to scheduled tribes compare with the non- tribal children: a secondary data analysis using the Comprehensive National Nutritional Survey (CNNS) 2016-18. - Pavithra H; Bhargava Madhavi; Dinachandra Konsam (Wolters Kluwer Medknow Publications, 2024)
Background: Scheduled tribes (ST) constitute 8.6% of India's population. Disproportionate burden of undernutrition is found among these socially disadvantaged population. objectives: To compare the nutritional status of under-5 ST children with children belonging to other castes (non-tribal) using data from Comprehensive National Nutritional Survey (CNNS) 2016-18. Methodology: We selected relevant demographic and anthropometric variables from the CNNS dataset and dichotomized it into non-tribal and tribal. World Health Organization (WHO) Anthro software was used to calculate the z-scores; weight-for-height (WHZ), weight-for-age (WAZ), height-for-age (HAZ). We estimated the proportion of wasting, underweight and stunting in these two sets of children. The mean z-scores between non-tribal and tribal children and that between girls and boys within these subsets were tested using student t-test. Results: Valid heights were available in 28,568 non-tribal and 7155 tribal children and the corresponding weights were available in 28144 and 6956 children respectively. The mean (SD) HAZ, an indicator of long-term nutrition, was -1.12 (1.58) in non-tribal children and -1.21 (1.71) in tribal children (p:<0.001) Prevalence of stunting in tribal children (31.6%; 95%CI: 30.6, 32.7) was higher than that in non-tribal (27.1%; 95%CI: 26.6, 27.6). Due to poor heights, wasting was less in tribal children (12.8%; 95%CI: 12, 13.6) compared to the non-tribal (14.5%; 95%CI: 14.1, 15). The non- tribal girls had better mean (SD) WHZ, -0.75 (1.3) and WAZ, -1.17 (1.26) than boys (p=0.01, 0.045 respectively). The heights between the boys and girls were comparable in the non-tribal subset whereas, it was better in tribal girls; mean HAZ being -1.15 (SD:1.69) in girls and -1.27, (SD:1.72) in boys (p<0.0029). Conclusion: The under-5 tribal children were significantly shorter than their non-tribal counterparts. Long term nutrition as depicted by heights was similar in boys and girls in non-tribal subset but tribal girls performed better than the boys.